Digest: Evolution of shape and leverage of bird beaks reflects feeding ecology, but not as strongly as expected. (25th January 2019) - Van Wassenbergh, Sam; Baeckens, Simon
Abstract: Is feeding ecology the main driver of beak diversification in modern birds? Taking a broad‐scale interspecific comparative approach, Navalón et al. (2019) found a relationship between feeding ecology (diet and feeding behavior) and beak morphology (shape and leverage), although much of the observed variation remained unexplained. This low explanatory power may suggest that variation in the multitude of nonfeeding functions of the beak also influences its evolution.